The Lost Sun : The United States of Asgard Book 1 - Gratton, Tessa (New York Ember, 2013)
"In an alternate U.S.A. (the United States of Asgard), Soren Bearskin, the son of an infamous beserker, and Astrid Glyn, daughter of a renowned seer, embark on a road trip to find Baldur, the missing god whose absence has caused panic throughout the country."
Keywords: Mythology, Norse -- Prophets -- Fate and fatalism